Heterometallic multinuclear nodes directing MOF electronic behavior. Issue 28 (2nd July 2020) - Ejegbavwo, Otega A.; Berseneva, Anna A.; Martin, Corey R.; Leith, Gabrielle A.; Pandey, Shubham; Brandt, Amy J.; Park, Kyoung Chul; Mathur, Abhijai; Farzandh, Sharfa; Klepov, Vladislav V.; Heiser, Brittany J.; Chandrashekhar, Mvs; et al.
Abstract : Metal node engineering in combination with modularity, topological diversity, and porosity of metal–organic frameworks (MOFs) could advance energy and optoelectronic sectors. Abstract : Metal node engineering in combination with modularity, topological diversity, and porosity of metal–organic frameworks (MOFs) could advance energy and optoelectronic sectors. In this study, we focus on MOFs with multinuclear heterometallic nodes for establishing metal−property trends, i.e., connecting atomic scale changes with macroscopic material properties by utilization of inductively coupled plasma mass spectrometry, conductivity measurements, X-ray photoelectron and diffuse reflectance spectroscopies, and density functional theory calculations. The results of Bader charge analysis and studies employing the Voronoi–Dirichlet partition of crystal structures are also presented. As an example of frameworks with different nodal arrangements, we have chosen MOFs with mononuclear, binuclear, and pentanuclear nodes, primarily consisting of first-row transition metals, that are incorporated in HHTP-, BTC-, and NIP-systems, respectively (HHTP 3− = triphenylene-2, 3, 6, 7, 10, 11-hexaone; BTC 3− = 1, 3, 5-benzenetricarboxylate; and NIP 2− = 5-nitroisophthalate). Through probing framework electronic profiles, we demonstrate structure–property relationships, and also highlight the necessity for both comprehensive analysis of trends in metal properties, and novel avenues for preparation of heterometallic multinuclear isoreticular structures, which are critical components for on-demand tailoring of properties in heterometallic systems.